Synchronous identification and successive detection of multiple traces with tunable coupling oscillators. (1st March 2022) - Xia, Cao; Wang, Dong F.; Song, Jie; Ono, Takahito; Itoh, Toshihiro; Maeda, Ryutaro; Esashi, Masayoshi
Highlights: Response amplitude of any coupled mode physically reflects multi-modal features. Identification and detection of multi-traces are realized via internal resonance. Measurement ranges and manufacturing errors are adjustable or compensable. High tunability, high sensitivity, and high linearity are achieved. A new metrological scheme is provided for measuring multiple traces. Abstract: Trace identification and detection of toxic, flammable, explosive substances, pollen allergens, as well as biological viruses is crucial for public health and safety, chemic production, and scientific research, etc. A single trace is detectable via various nonlinear resonance phenomena, while quantitative detection of two traces is physically limited by the trace ratio even with localized oscillators. We have discovered that, in internal resonance systems, response amplitude of any coupled mode physically reflects multi-modal features. In case of multi-mode coupled duffing oscillators, peaks and jumps in response amplitudes show great potential in synchronous identification and successive detection for multiple traces. With tunable magnetically coupled duffing oscillators, multiple traces are both experimentally and theoretically demonstrated to be synchronously identified and successively detected with multiplied frequency shifts. Measurement ranges and manufacturing errors are adjustable or compensable respectively only through turning the coupling strength. This work not only opens a new avenue in applications of nonlinear resonators, but also provides a new metrological scheme for synchronous identification and successive detection of multiple traces.